Proteomic Analysis of DNA Synthesis on a Structured DNA Template in Human Cellular Extracts: Interplay Between NHEJ and Replication‐Associated Proteins. Issue 3 (13th February 2020) - Janel‐Bintz, Régine; Kuhn, Lauriane; Frit, Philippe; Chicher, Johana; Wagner, Jérôme; Haracska, Lajos; Hammann, Philippe; Cordonnier, Agnès M
Abstract: It is established that short inverted repeats trigger base substitution mutagenesis in human cells. However, how the replication machinery deals with structured DNA is unknown. It has been previously reported that in human cell‐free extracts, DNA primer extension using a structured single‐stranded template is transiently blocked at DNA hairpins. Here, the proteomic analysis of proteins bound to the DNA template is reported and evidence that the DNA‐PK complex (DNA‐PKcs and the Ku heterodimer) recognizes, and is activated by, structured single‐stranded DNA is provided. Hijacking the DNA‐PK complex by double‐stranded oligonucleotides results in a large removal of the pausing sites and an elevated DNA extension efficiency. Conversely, DNA‐PKcs inhibition results in its stabilization on the template, along with other proteins acting downstream in the Non‐Homologous End‐Joining (NHEJ) pathway, especially the XRCC4‐DNA ligase 4 complex and the cofactor PAXX. Retention of NHEJ factors to the DNA in the absence of DNA‐PKcs activity correlates with additional halts of primer extension, suggesting that these proteins hinder the progression of the DNA synthesis at these sites. Overall these results raise the possibility that, upon binding to hairpins formed onto ssDNA during fork progression, the DNA‐PK complex interferes with replication fork dynamics in vivo.